2020
DOI: 10.1111/dth.13310
|View full text |Cite
|
Sign up to set email alerts
|

Consensus of Chinese experts on protection of skin and mucous membrane barrier for health‐care workers fighting against coronavirus disease 2019

Abstract: Health professions preventing and controlling Coronavirus Disease 2019 are prone to skin and mucous membrane injury, which may cause acute and chronic dermatitis, secondary infection and aggravation of underlying skin diseases. This is a consensus of Chinese experts on protective measures and advice on handcleaning-and medical-glove-related hand protection, mask-and goggles-related face protection, UV-related protection, eye protection, nasal and oral mucosa protection, outer ear, and hair protection. It is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
377
4
63

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(451 citation statements)
references
References 12 publications
7
377
4
63
Order By: Relevance
“…Different methods can be chosen for the disinfection of hands and surfaces. Ultraviolet (UV) disinfection, hot water bath with temperature of [ 56°C (132.8°K) for 30 min, chlorine-containing disinfectants, peracetic acid or 75% ethanol can effectively inactivate the virus [136][137][138].…”
Section: Recommendations On Decontamination and Cleaningmentioning
confidence: 99%
“…Different methods can be chosen for the disinfection of hands and surfaces. Ultraviolet (UV) disinfection, hot water bath with temperature of [ 56°C (132.8°K) for 30 min, chlorine-containing disinfectants, peracetic acid or 75% ethanol can effectively inactivate the virus [136][137][138].…”
Section: Recommendations On Decontamination and Cleaningmentioning
confidence: 99%
“…Heat and dehydration were major complications of both goggles and face shields application during the Ebola outbreak [7]. Other dermatologic side-effects such as pressure injury, contact dermatitis, urticaria, xerosis and aggravation of underlying dermatosis might occur due to the impairment of the skin integrity during mechanical trauma of goggles [8]. A study by Lan et al, [2] revealed that 87.9% of HCWs, who were wearing goggles for more than 6 hours, developed skin reactions on their nasal bridge.…”
Section: To Editormentioning
confidence: 99%
“…3 To this end, several measures to avoid hand dermatitis, maceration, and erosion due to PPE and handwashing during the pandemic have been proposed. 4 Although the application of hand cream/moisturizers on intact skin after hand washing is recommended, 6 only 22.1% applied hand creams after washing. 3,4 Education of HCWs regarding proper skin care management may be effective in preventing occupational skin disorders.…”
Section: The Role Of Occupational Dermatology In the Covid-19 Outbreakmentioning
confidence: 99%